The Effectiveness of Internal Control over Lease Accounting: Case Study of PSAK 116 Lease - Alexander, Ivan; Mita, Aria Farah (E-Jurnal Akuntansi; Vol 35 No 4 (2025), 2025)
The objective of this study is to evaluate the internal control procedures implemented by PT ABC in relation to PSAK 116: Lease, with a focus on completeness and accuracy as outlined by the COSO framework and the Three Lines Model. According to the external auditor's examination, PT ABC has faced deficiencies in Internal Control Over Financial Reporting, particularly regarding the completeness and accuracy of lease recording for two reporting periods. Effective remediation efforts have not been found, which poses a risk to the reliability of the financial report. This study employs a descriptive qualitative analysis method to gather direct insights from the management perspective. The findings suggest that key factors in enhancing internal control deficiencies include monitoring and evaluation of the effectiveness of internal control and strengthening the internal audit function. Additionally, fostering interaction, communication, and collaboration among management and internal functions is crucial for establishing effective internal control. Keywords: Internal Control; Lease Accounting; Control Deficiency, Three Line Model.